2008
DOI: 10.1002/art.23809
|View full text |Cite
|
Sign up to set email alerts
|

Percent true calcium absorption, mineral metabolism, and bone mass in children with arthritis: Effect of supplementation with vitamin D3 and calcium

Abstract: The findings of this study indicate that percent true calcium absorption is low-normal in children with arthritis. Vitamin D3 at 2,000 IU/day increases serum 25(OH)D and calcium levels but does not improve bone mass accretion. Calcium at 1,000 mg/day also failed to improve bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
19
0
3
Order By: Relevance
“…In a U.S. study, black adolescent girls had lower 25-hydroxyvitamin D concentrations than white girls, but calcium absorption and retention were unrelated to 25-hydroxyvitamin D or 1,25-dihydroxyvitamin D concentrations (29). In a group of children with arthritis, supplemental vitamin D 3 , 2000 IU/d for 6 months, had no effect on calcium absorption, irrespective of whether it was given with supplemental calcium (30). One strength of our study is it is the first to compare directly the effect of both vitamin D 2 and vitamin D 3 administration on calcium absorption in children.…”
Section: Discussionmentioning
confidence: 97%
“…In a U.S. study, black adolescent girls had lower 25-hydroxyvitamin D concentrations than white girls, but calcium absorption and retention were unrelated to 25-hydroxyvitamin D or 1,25-dihydroxyvitamin D concentrations (29). In a group of children with arthritis, supplemental vitamin D 3 , 2000 IU/d for 6 months, had no effect on calcium absorption, irrespective of whether it was given with supplemental calcium (30). One strength of our study is it is the first to compare directly the effect of both vitamin D 2 and vitamin D 3 administration on calcium absorption in children.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study showed significantly lower osteocalcin and alkaline phosphatase concentrations in individuals with JIA compared to controls, suggesting reduced bone formation (14). Lower calcium concentrations in the JIA group, with no difference in 25(OH)D concentrations may be explained by the reduced capacity for mineral absorption described in children with arthritis (17). A study in animal We did not find an association between 25(OH)D concentrations with either disease activity or duration.…”
Section: Discussionmentioning
confidence: 56%
“…However, only a few studies have assessed the serum concentrations of 25(OH)D in children and adolescents with JIA (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…En otro estudio se pone de manifiesto que la suplementación con 2.000 UI de vitamina D3 diarias, aumenta la concentración sérica de 25 (OH) D y los niveles de calcio, pero no mejoran la masa ósea. Resultados similares se obtuvieron con la suplementación de 1.000 mg de calcio al día 27 .…”
Section: Lactancia Maternalunclassified